Multiple identities and crime: A study of Antillean women and girls in the Netherlands - Althoff, Martina (European Journal of Criminology, 2013)
The concept of intersectionality refers to the constructionist approach, which considers gender, class and race as categories of social inequality that cannot be added together but that intersect and construct each other. Social categories construct the social identities that affect what motivates people and how they operate. The question is how multiple identities come together in the context of crime? The paper reports the findings of a qualitative study that explored the concept of intersectionality when analysing crime. The study analysed the court files of Antillean women and girls living in the Netherlands and tried to find an explanation for their crime patterns in their struggle with their identity.
Keywords: antilles; approches et analyses; criminologie; discipline; europe; femmes* immigrantes; genre; identités LGBTQIA2+; identités de genre; intersectionnalité; inégalités; pays-bas; ressource en ligne; régions géographiques; sciences humaines; systèmes d'oppression; thématiques; violences; étude qualitative

La justice réparatrice et les victimes d’actes criminels : actes du colloque tenu le 28 mars 2002 à Montréal - Wemmers, Jo-Anne; Cyr, Katie (2002)
Keywords: amériques; belgique; canada; criminologie; discipline; europe; justice réparatrice; ressource en ligne; régions géographiques; sciences humaines; sofia